The EVENDOL Pain Scale Validation for Acute Non‐Procedural Neonatal Pain in Term Neonates: Reliability and Validity in Maternity Wards - Lucie Calamy; Elisabeth Fournier‐Charrière; Patricia Martret; Patricia Cimerman; Claire Boithias; Thierry Debillon; Ricardo Carbajal; Bruno Falissard; Elizabeth Walter‐Nicolet (Paediatric & Neonatal Pain)
ABSTRACT The assessment of acute non‐procedural pain in term neonates in maternity wards is challenging due to the difficulty in selecting an appropriate scale and the time‐consuming nature of the process. This can lead to inadequate neonatal pain management. To validate the EValuation ENfant DOuLeur (EVENDOL) pain scale for acute non‐procedural pain in term neonates in maternity units by comparing it with the Echelle Douleur et Inconfort du Nouveau‐né (EDIN) used as a reference. We hypothesized that EVENDOL would be equivalent to EDIN in assessing acute non‐procedural neonatal pain, with better appearance. Prospective multicentric non‐interventional open study. Term neonates over 37 weeks' gestation in the delivery room and postnatal care units, with or without acute non‐procedural pain, before and after analgesia. Cronbach's α coefficient, intraclass correlation (ICC), and correlation between EVENDOL and EDIN scores, documented by the researchers and the caregivers at rest and mobilization, before and after oral paracetamol, were measured. Ninety‐one neonates were included: 48 (51%) had pain and 43 (47%) had no pain. Before analgesia, the Cronbach coefficient was above 0.80, the ICC (25th–75th interquartile ranges [IQ]) were 0.84 (0.77–0.89) and 0.90 (0.85–0.93) at rest and mobilization, respectively. Seventeen patients received oral acetaminophen and were re‐assessed. Psychometric values remained good after analgesia (Cronbach coefficient above 0.80, ICC [IQ]: 0.65 [0.26–0.85] and 0.76 [0.45–0.91]) at rest and mobilization, respectively. The feasibility and ease of use were better for EVENDOL for researchers and caregivers. EVENDOL is suitable for the assessment of acute non‐procedural neonatal pain for term neonates in the maternity wards. Trial Registration: ClinicalTrials.gov identifier: NCT02819076, registered in June 2016 as EVENDOL scale validation for at term newborn